Falas que vêm das salas e falas que vêem as salas: o que dizem os professores de ciências e matemática sobre a psicologia da educação na formação docente - DIAS, Luiz Carlos de Carvalho (2006)
In this research we apply a narrative approach qualitatively inspired as a compass to analyses and interpretations conducted by us. We place ourselves projecting the importance of research shape in autobiographical terms concerning teachers of Science and Mathematics in a continued education course at a post graduation level. We study along the subjects some aspects in Psychology of Education, in the beginning of teachers training, considered important for these teachers by teachers emotional attribution of value, sense and meaning in order to care about their present teaching practice. We stress the impressions of eight teachers in a Latu Sensu course Specialization in Mathematical Education, obtained through semi-structured collective interview taken from the first group and questionnaires applied to the second group, some theoretical-methodological content, focused on narrative terms, related to personal teaching practice and based on the idea of preparing brainy teachers that consider Psychology, especially, as a proposal for a development leading to a brainy practice. The analyses produced by us reveal auto-reflected and reflexive terms built on methodological-theoretical contents oriented to teaching practice being satisfactory and conceptual-theoretical contents not oriented to teaching practice labeled as insufficient by teachers interviewed, explained by their questioning on their interaction to teenager students and related to this group being numerous and emergent in medium and fundamental teaching level in common classrooms, as well in young and adults education. A kind of education by self-knowledge meant to heterodox knowledge, theorization of their teaching practice and study of reflexive teaching practices or specific psychological theories that make them care about their practice as propositions and principles of schooling. In research terms, to follow initial educational background by life experiences means to find the shape and attitude for schooling, sensitivity and sharp thought, in a significant come-to-be when teachers direct their life experiences in reflexive learning to teaching practice, not only attempting to reshape an self-image, but looking for a perception of the self and the other in schooling.